Covid-19 Pendemic (Incidence, Risk factors and Treatment) - Fares M.S Muthanna; Abdul Samad (CV. Multi Kreasi Media, 2022)
At the end of 2019, the coronavirus disease (COVID-19) was observed in Wuhan, China. It has since distributed to over 220 countries and territories, prompting the World Health Organization (WHO) to announce it a worldwide outbreak . It is generated by the unique SARS-CoV-2 coronavirus and resulted in a global, unexpected, and substantial increase in hospitalizations for bronchitis with organ dysfunction illness. This brief article summarizes the existing studies on COVID-19 incidence, risk factors, and management.